Rent burden and the Great Recession in the USA. (January 2018) - Colburn, Gregg; Allen, Ryan
In the aftermath of the recent recession, the percentage of households facing rent burden in the USA reached historically high levels, while cost burden for owners has shrunk. This study uses two panels from the Survey of Income and Program Participation (SIPP) to compare the prevalence, distribution and household responses to the phenomenon of rent burden in the USA in the years immediately before and after the Great Recession. Results suggest that rent burden has become more prevalent after the recession and that income, household composition and location are major drivers of this phenomenon, both before and after the recession. Results also indicate that exiting rent burden was more difficult in the years after the recession and that an increasingly common coping mechanism for rent burdened households is to increase their household sizes. These results indicate that renters have experienced increased financial stress related to their housing. This finding is notable given the lack of policy responses that address hardship among renter households in contrast to the privileged status enjoyed by homeowners in the policy domain.